Upaya Meningkatkan Asertivitas Melalui Layanan Konseling Kelompok Dengan Teknik Asertif Training Pada Siswa Asuh Kelas X DPIB 2 SMK Negeri 1 Sampang - Hidayatullah, Syaiful (Universitas Nusantara PGRI Kediri, 2020)
Assertive behavior is important for individuals. Assertive behavior reflects how individuals are able to recognize themselves and be honest in dealing with or interacting with others. Assertive behavior leads individuals to be able to appreciate the expression of positive and negative feelings of themselves and others and to be able to exercise self-control without guilt. The purpose of this study was to determine the efforts to increase assertiveness through group counseling services with assertive training techniques for students. In this study, the research subjects were students who had a low level of assertiveness in class X DPIB 2 SMK Negeri 1 Sampang. This research took place in two cycles. The data collection technique used a student activeness questionnaire. The data analysis method used to analyze the level of success or the percentage of giving reinforcement to student assertiveness was done by providing an evaluation questionnaire. From the results of cycles I and II, there was an increase in the criteria for rigor from